Perencanaan Bahan Baku Produksi Menggunakan Metode Material Requirement Planning (MRP) Studi Kasus Teh Botol Sosro - Simanjuntak, Sarah Stefhanie; Zaharuddin, Zaharuddin; Puspita, Riana (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
Raw material inventory is a serious problem for manufacturing companies. Shortages of raw materials can stop production, while inventories that are too large cause high storage costs and result in idle capital. Therefore, research entitled "Planning Raw Materials for Production of Sosro Bottled Tea Using the Material Requirement Planning (MRP) Method at Sinar Sosro Deli Serdang" was carried out. The aim of this research is to determine the planning of the amount of raw materials needed for production. This research is descriptive with primary and secondary data. The research results show that the raw material requirements for the production of Teh Botol Sosro for the period January 2022-December 2022 are as follows: Sugar 5,213,184 kg, Dry Tea 365,329 kg, Water 6,455,592,000 ml, Bottle Cap/Crown Cork 2,934,600 pcs, Bottles 2,934. 600 pcs, and Krat 1,222,650 pcs. Lot size calculations using the Lot for Lot (LFL) and Period Order Quantity (POQ) methods show that the POQ method is more economical with a minimum cost of IDR 1,944,412.59. Keywords: Lot For Lot, Material Requirement Planning (MRP), Period Order Quantity, Raw Material Planning